IoT-Based Electrical Parameter Monitoring System for Railway Level Crossing Gate Panels - M. Afif Amalul Arifidin; Ulfatul Rahmad; Akhwan Akhwan; Teguh Arifianto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
To speed up the handling of disruptions and improve safety at level crossings, an alternative system is needed to help officers deal with disruptions at level crossings. The implementation of an Internet of Things (IoT) system can be a solution for monitoring the actual condition of level crossings in real time. This system was developed using an ESP 32 microcontroller, an INA226 sensor, and an ACS712 sensor to measure battery voltage, motor voltage, and charger current. Monitoring is conducted through a website equipped with a Threshold Detection method to send early notifications via Telegram. Functionality testing using the black box method showed that the system operates as designed. Sensor accuracy testing revealed that the INA226 sensor has a voltage accuracy of 99.25%. However, the ACS712 20A sensor showed lower accuracy (65.26%) due to incorrect sensor type selection and noise during calibration.